Gluteal Fascial Advancement for Pilonidal Cyst Disease: A 10-year Review. Issue 7 (July 2016) - Powell, Benjamin C.; Webb, Colin B.; Ewing, Joseph A.; Smith, Dane E.
Elective excision of noninfected pilonidal cysts has historically been plagued by a high rate of complications, such as wound breakdown and recurrence. Debate remains regarding the most effective method of wound closure. We previously reported a small group of patients (n = 17 out of 83 patients) in which a novel technique decreased wound complications and recurrence. The purpose of this article was to build on that prior study by evaluating the utility of the gluteal fascial advancement method to decrease complications over a 10-year period. All patients who underwent elective pilonidal cyst excision from 2008 to 2015 were retrospectively reviewed (n = 150); this was added to the data from 2004 to 2007. Patients were divided into two cohorts: those who underwent elective excision with simple closure (n = 172) and those who underwent bilateral gluteal fascial advancement flaps (n = 61). Primary end points included recurrence and dehiscence. Overall demographic characteristics were statistically comparable between groups. The rate of recurrence was not significantly different between groups. However, wound closure using bilateral gluteal fascial advancement flaps was associated with a significantly lower rate of dehiscence when compared with standard primary closure (12% vs 40%, P < 0.001). The use of bilateral gluteal fascial advancement flaps is a superior method for closing elective pilonidal cyst excisions.